RETRACTED: : Neural network to investigate gaming addiction and its impact on health effects during the COVID-19 Pandemic (Periodicals of Engineering and Natural Sciences, 2022)
This article has been retracted. After a thorough investigation, the listed authors of “Neural network to investigate gaming addiction and its impact on health effects during the COVID-19 Pandemic” committed a serious misconduct of standards of publication ethics, since they submitted a contribution that did not satisfy originality.